“RELATION OF MATERNAL LITERACY AND KNOWLEDGE ABOUT ORS WITH ACUTE DIARRHEA AND ITS OUTCOME: A HOSPITAL BASED TERTIARY CARE CENTER STUDY IN RAJASTHAN” - Dr. Deepak Kumar Pareek; Dr. Pardeep Kumar; Dr. Vishakha Dharambir Singh; Dr. Harshita Pandey; Dr. Mohit Dadhich; Dr. Rajendra Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Acute diarrheal illness continues to be one of the primary contributors to morbidity and mortality among children under five years of age in developing nations. Objective: This study aimed to explore the relationship between maternal literacy, awareness of oral rehydration solution (ORS), and outcomes in under five children admitted with diarrhea. Methods: A prospective observational study was carried out over one year at SHKBM Hospital, Jhalawar, including 400 mothers of children aged 6 months to 5 years. A structured interview schedule was used to assess maternal literacy, knowledge regarding ORS, awareness of danger signs, hygiene and feeding practices. Data were analyzed using SPSS 25. Results: Of 400 participants, 52.8% were literate. Maternal literacy was significantly associated with lower rates of severe dehydration (p < 0.001). Only 57% mothers knew correct ORS preparation, and 49% reported starting ORS the same day of diarrhea onset. About 70.5% could identify danger signs. Children of illiterate mothers had higher prevalence of severe dehydration (22/189 vs. 4/211). Rural residence was significantly associated with more severe dehydration (p = 0.007). Conclusion: Although awareness of diarrhea prevention and ORS use was moderate, significant gaps persist in correct ORS preparation and timely administration. Maternal literacy and health education strongly influence diarrhea outcomes. Focused health education and community-based awareness programs are essential to reduce morbidity and mortality.